(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
Over time, the pace of human life changes. The development of science and production leads to international integration. Every country that does not want to lag behind in development joins the process of globalization. Globalization is a product of the integration of the peoples of the world in all areas